Analysis of the Websites of Public Secondary Schools of Cantabria (Spain) - Víctor Tardío-Crespo; Carmen Álvarez-Álvarez (Universidad Autónoma de Madrid, 2018)
With the profound social transformation that has led to the integration of ict in our day to day, modes of communication in the educational world have evolved towards the Internet and towards a networked universe. This fact has turned the web pages of educational centers, among other elements, into catalytic tools for the school panorama. In order to know the presentation of the contents of these pages to their different audiences a research has been carried out in the present work to analyze the web sites of the forty-eight public secondary education centers of the Autonomous Community of Cantabria. The analysis has been carried out in relation to its content, organization, navigation, appearance, differentiation, speed, utility and accessibility. The results obtained reveal really encouraging figures, such as that only 27'08% and 14'58% show deficiencies in their organization and clarity. It should be noted on the other hand, that the average score of the websites in utility for the interested parties is of an 8'19 valuation as a whole. We are generally in front of websites with a clear progressive, active and interactive character, although it is possible to conclude by suggesting some improvements such as facilitating a richer dissemination of useful resources, as well as providing a greater exposure of the most important plans and projects of the center in some section of the web pages of educational centers.